Defying death: incorporating fossils into the phylogeny of the complex thalloid liverworts (Marchantiidae, Marchantiophyta) confirms high order clades but reveals discrepancies in family‐level relationships. (9th November 2020) - Flores, Jorge R.; Bippus, Alexander C.; Suárez, Guillermo M.; Hyvönen, Jaakko
Abstract: In recent years, the use of extensive molecular and morphological datasets has clarified the phylogenetic relationships among the orders of complex thalloid liverworts (Marchantiidae). However, previous studies excluded extinct taxa; thereby, undersampling the actual taxonomic diversity of the group. Here, we conducted a total‐evidence analysis of Marchantiidae incorporating fossils. The combined dataset consisted of 11 genes—sampled from the nuclear, mitochondrial and plastid genomes—and 128 morphological characters. Sixty‐two species, representing all classes and orders within Marchantiophyta and genera within Marchantiidae were included in the analyses. Six fossils were scored from literature: two assigned to the outgroup ( Metzgeriothallus sharonae and Pallaviciniites sandaolingensis ) and four to the ingroup ( Marchantites cyathodoides, M. huolinhensis, Ricciopsis ferganica and R. sandaolingensis ). Tree searches were conducted using parsimony as the optimality criterion. Clade sensitivity was assessed across a wide range of weighting regimes. Also, we evaluated the influence of fossils on the inferred topologies and branch support. Our results were congruent with previously inferred clades above the order level: Neohodgsoniales was sister to a clade formed by Sphaerocarpales and Marchantiales. However, relationships among families within Marchantiales contradicted recent studies. For instance, a clade consisting of Monosoleniaceae, Wiesnerellaceae and Targioniaceae was sister to the morphologically simple taxa instead of being nested within them as in previous studies. Novel synapomorphies were found for several clades within Marchantiales. Outgroup fossils were more influential than Marchantiidae fossils on overall topologies and branch support values. Except for a single weighting scheme, sampling continuous characters and down‐weighting characters improved fossil stability. Ultimately, our results challenge the widespread notion that bryophyte fossils are problematic for phylogenetic inference.